Biorefinery of inorganics : recovering mineral nutrients from biomass and organic waste - Meers, Erik, 1976-; Michels, Evi, 1980-; Rietra, Rene, 1967-; Velthof, Gerard, 1964- (Wiley series in renewable resources, 2020)
"As part of the move towards a bio-based economy, it is important to recycle the valuable nutrients that currently end up in waste streams. Nutrient resources are depleting and significant amounts of fossil energy are required for the production of synthetic fertilizers, but waste streams including agricultural waste, wastewater/sewage and municipal waste are significant sources of nutrients. The production of biogas through anaerobic digestion also produces nutrient-rich digestates, which have the potential for use as green fertilizers in agriculture"--